2022
DOI: 10.1136/ejhpharm-2022-003297
|View full text |Cite
|
Sign up to set email alerts
|

The role of clinical trials in the sustainability of the Italian national health service cancer drug expenditure

Abstract: Objective Clinical trials offer new and potentially more effective therapeutic options for cancer patients and a potential cost-saving opportunity, especially considering that trial drugs are provided free-of-charge. The aim of this study was to analyse drug-related cost savings in clinical trials in a cancer institute over a 3 year period. The cost savings relate to the pharmaceutical expenditure of our centre, IRCCS Istituto Romagnolo per lo Studio dei Tumori (IRST) “Dino Amadori”. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Again, the timeline was not the same and our site was not involved in many studies at the time of this work in onco-gynaecology (three clinical trials). For the other most recent studies,12–14 major cost savings were observed for melanoma, breast cancer and genitourinary cancer. The difference between repartition could be explain by the specific expertise of each centre.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the timeline was not the same and our site was not involved in many studies at the time of this work in onco-gynaecology (three clinical trials). For the other most recent studies,12–14 major cost savings were observed for melanoma, breast cancer and genitourinary cancer. The difference between repartition could be explain by the specific expertise of each centre.…”
Section: Discussionmentioning
confidence: 99%
“…These legal requirements could lead to a new opportunity for clinical trials, namely the potential for cost savings related to the coverage of ‘best standard of care’ (BSC) expenditure. The literature reports studies primarily focused on cost saving in oncology studies,5–14 with a variable follow-up period (1 to 18 years),5–14 with a variable number of patients (136 to 3195 patients)5–14 and of the trials involved (5 to 88 trials) 5–14. Finally, only a few studies take into account the avoided costs of all clinical trials15–17 and over a wider follow-up period (1 to 2 years).…”
Section: Introductionmentioning
confidence: 99%
“…Academic research has been considered a source of sustainability of public healthcare systems [25,26], with trial sponsors providing tangible benefits [27,28]. However, quantification of DCA in cancer patients treated in clinical trials has not been consistently documented, particularly due to deficient infrastructure information systems of hospitals, and because trial drugs provided by sponsors are not systematically included in pharmacoeconomic analyses of cancer medications [29].…”
Section: Discussionmentioning
confidence: 99%